Pendidikan Hukum Dalam Sosialisasi Vaksinasi Sebagai Upaya Penanggulangan Penyebaran Covid-19 - siti fatimah; Toni Harsan; Ika Murtiningsih (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
The understanding of vaccination in the village community is still unclear, so it is necessary to socialize the regulations on vaccination. Doubts that often arise among the village community regarding receiving the vaccine are fear of the impact that will be caused after the community receives the vaccine. In connection with the many cases of impact due to vaccination that occurred in all corners of the world, some villagers fear, do not believe, and even refuse to be vaccinated. This legal education in vaccination socialization in Jagan Village, Bendosari District, Sukoharjo aims to make all village communities aware of the law to receive vaccines in an effort to overcome the spread of Covid-19 and as an effort to improve lifestyle so that it can return to normal. The vaccination socialization was carried out using lecture and discussion methods. Legal education activities in the dissemination of Covid-19 vaccination in Jagan village, Bendosari, Sukoharjo are the right steps to motivate and provide in-depth information on Covid-19 vaccination to the participants of Angga Mandiri members, Jagan Village. The participants are also ready to socialize the vaccination movement to residents so that they are ready to take part in the implementation of the Covid-19 vaccination. And, as a result of this service, the total number of recipients and participating in the Covid-19 vaccine vaccination in Jagan Village, Bendosari Sukoharjo was 325 people.